Heat waves in the Colombian Caribbean: A public health problem? - Pérez-Anaya, Oskarly; Wilches-Visbal, Jorge Homero; Álvarez-Miño, Lídice (Revista Cuidarte, 2023)
Highlights• If a frog is submerged in a container and gradually heats it up, it will try to adapt until it dies; this is probably the situation faced by more and more human populations.• Human activities have significantly impacted the environment, ecosystems, and plant and animal diversity throughout history.• The planet’s average temperature is estimated to increase by about 3.2 °C this century, severely affecting human health.• One of the events attributed to climate change is heat waves.A popular belief states that if frog is submerged in a container and gradually heats it up, it will try to adapt until it dies; this is probably the situation faced by more and more human populations. As stated by thousands of scientists, academics, and researchers worldwide, the planet’s warming is directly related to climate change.How to cite this article: Pérez-Anaya Oskarly, Wilches-Visbal Jorge Homero, Álvarez-Miño Lídice. Olas de calor en el Caribe colombiano: ¿un problema de salud pública? Revista Cuidarte. 2023;15(1):e3199.  http://dx.doi.org/10.15649/cuidarte.3199
Keywords: Climate Change; Heat Wave; Thermosensing; Caribbean Region; Colombia